2015
DOI: 10.1158/1078-0432.ccr-14-1128
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtypes of Clear Cell Renal Cell Carcinoma Are Associated with Sunitinib Response in the Metastatic Setting

Abstract: Purpose: Selecting patients with metastatic clear-cell renal cell carcinoma (m-ccRCC) who might benefit from treatment with targeted tyrosine kinase inhibitors (TKI) is a challenge. Our aim was to identify molecular markers associated with outcome in patients with m-ccRCC treated with sunitinib.Experimental Design: We performed global transcriptome analyses on 53 primary resected ccRCC tumors from patients who developed metastatic disease and were treated with first-line sunitinib. We also determined chromosom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
234
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(251 citation statements)
references
References 41 publications
16
234
0
1
Order By: Relevance
“…The tumor microenvironment and immune surveillance system are thought to play an important role for tumor growth and progression and also to be involved in the treatment responses to targeted therapy [20,21]. Beuselinck et al [10] demonstrated that the ccrcc4 molecular subtype was closely related to a poor response to sunitinib treatment. This tumor subtype also showed increased activity in the hypoxia pathway, a strong inflammatory immune environment, high levels of regulatory T-cell markers, such as Foxp3, increased numbers of myeloid-derived suppressor cells, and high PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tumor microenvironment and immune surveillance system are thought to play an important role for tumor growth and progression and also to be involved in the treatment responses to targeted therapy [20,21]. Beuselinck et al [10] demonstrated that the ccrcc4 molecular subtype was closely related to a poor response to sunitinib treatment. This tumor subtype also showed increased activity in the hypoxia pathway, a strong inflammatory immune environment, high levels of regulatory T-cell markers, such as Foxp3, increased numbers of myeloid-derived suppressor cells, and high PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study analyzed the molecular subtype of primary CCRCC in patients who developed metastatic tumors and were treated with sunitinib. The study showed that ccrcc1/ccrcc4 tumors had a lower response rate, shorter overall survival (OS), and shorter progressionfree survival (PFS) than ccrcc2/ccrcc3 tumors [10]. Among the molecular subtypes analyzed, ccrcc4 tumors exhibited sarcomatoid differentiation with a strong inflammatory, Th1-oriented, but suppressive immune microenvironment, along with high expression of programmed death-1 (PD-1) and its ligand, PD-L1 [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathology slides were reviewed by expert genitourinary pathologists. All tumour samples were classified according to the molecular ccrcc1-4 classification (Beuselinck et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our team has described an expression profile-based classification of ccRCCs with four robust molecular subgroups (Beuselinck et al, 2015). These subtypes are associated with distinct RR, mPFS and mOS when treated with sunitinib in first-line metastatic setting.…”
mentioning
confidence: 99%